Pengaruh Profitabilitas, Leverage dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Makanan dan Minuman Yang Terdaftar di Bei Tahun 2014-2018 (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2020)
A good company can be seen from the corporate value, currently business competitionbetween companies is very tight so it can’t be separated from social, political, technologi andeconomic depelopment. The company must be more effective and efficient in carrying out thecompany’s operational activities as well as improving performance and innovating byincreasing shareholder prosperity and to increase company growth through increasingcorporate value.In this study profitability is measured using Return On Assets (ROA), leverage ismeasured using a Debt to Equity Ratio (DER), firm size is measured using Ln Assets andcorporate value is measured using Tobin’s Q. The purpose of this study was to obtainempirical evidence from the effect of profitability, leverage and firm size on corporate value.The research method used is descriptive and verification analysis. The population inthis study are manufacturing companies the sub sector food and beverage listed on theIndonesia Stock Exchange for period 2014-2018. While the sample in this study wasdetermined by purposive sampling method so that 11 sample companies were obtained. Theclassic assumption test, multiple linier regression analysis, determination coefficient andhypothesis test to partial and simultaneously.The results of this study indicate that profitability significant effect on corporate value,leverage significant effect on corporate value and firm size have no significant effect oncorporate value. Profitability, leverage and firm size significant effect on corporate value